The Management of Iatrogenic Obstructive Sleep Apnoea Syndrome Following Bimaxillary Surgery in a Patient with Cleft Lip and Palate. Issue 5 (July 2016) - Gerbino, Giovanni; Gervasio, Fernando Carmine; Blythe, John; Bianchi, Francesca Antonella
Abstract : Abstract: A 26-year-old man presented with a 6-year history of severe obstructive sleep apnoea syndrome followed a bimaxillary osteotomy procedure for a class III skeletal pattern. The patient was born with a unilateral cleft lip and palate and underwent primary lip and palate repair and later a pharyngeal flap for severe velopharyngeal insufficiency. Surgical management of obstructive sleep apnoea syndrome with conventional osteotomy, in cleft lip and palate patients, is a difficult problem. Distraction osteogenesis may provide a safer alternative. The authors describe and discuss the indications and the technical challenge of a multistage treatment protocol with distraction osteogenesis.